FORMATION OF COGNITIVE AND INTELLECTUAL COMPETENCE AS A FACTOR OF THE PROFESSIONAL COMPETENCE OF THE FUTURE SPECIALIST - Zabolothy, O.; Zabolotna, A. (SWorld-Ger Conference proceedings, 2023)
The article clarifies the essence of the concept of cognitive-intellectual competence as an important factor in the professional competence of a future specialist. An analysis of the professional competence of the future specialist was carried out. The st